EMPLOYEE ENGAGEMENT, DISIPLIN, DAN REWARD TERHADAP KINERJA PEGAWAI DI PT CITRA MARGATAMA SURABAYA: (EMPLOYEE ENGAGEMENT, DISCIPLINE, AND REWARD ON EMPLOYEE PERFORMANCE AT PT CITRA MARGATAMA SURABAYA) - Firdaus, Vera; Djuwantoro, Vani Sofiah; Sumartik, Sumartik (UPT Penerbitan Universitas Jember, 2024)
The research conducted aims to determine the influence of employee engagement, discipline and rewards on employee performance at PT Citra Margatama Surabaya. This research uses quantitative methods. The population of employees at the Toll Road Business Entity (BUJT, namely PT Citra Margatama Surabaya in the toll road operational and service division. The number of research respondents was 114 which were obtained using a purposive technique which was adapted to the research objectives. Primary data was obtained from a questionnaire which was then obtained using the program SPSS 25. The research results show that Employee Engagement, Discipline and Rewards have a positive and significant effect on employee performance at PT Citra Margatama Surabaya. This research proves the influence of Employee Engagement, Discipline and Rewards on Increasing Employee Performance.